2017
DOI: 10.1590/0034-737x201764030009
|View full text |Cite
|
Sign up to set email alerts
|

Produção de sementes de soja enriquecidas com molibdênio

Abstract: Production of soybean seeds enriched with molybdenumThe objective was to evaluate the production of seeds enriched by the application of foliar molybdenum (Mo) doses and the growth and yield of plants resulting from the seeds obtained in this cultivation. We used the cultivar BRS Valiosa RR and in the first year, we used three doses of molybdenum (0, 400, and 800 g ha -1 ), with four replications. With the harvested seeds, three lots of seeds with different Mo contents were formed (9.27; 51.56, and 65.43 mg kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The use of molybdenum on edible bean seeds (3 g kg -1 seeds), also increased shoot dry matter production by 3.91 g (Matoso;Kusdra, 2014). Oliveira et al (2017), in the soybean crop, concluded that application rates of Mo from 25 to 50 g ha -1 through the leaves are sufficient to increase yield. However, fertilization with molybdenum did not change dry matter production of leaves and seeds or seeds per plant (Table 2), indicating lower demand of molybdenum for chickpea production or adequate natural supply of this nutrient via soil.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of molybdenum on edible bean seeds (3 g kg -1 seeds), also increased shoot dry matter production by 3.91 g (Matoso;Kusdra, 2014). Oliveira et al (2017), in the soybean crop, concluded that application rates of Mo from 25 to 50 g ha -1 through the leaves are sufficient to increase yield. However, fertilization with molybdenum did not change dry matter production of leaves and seeds or seeds per plant (Table 2), indicating lower demand of molybdenum for chickpea production or adequate natural supply of this nutrient via soil.…”
Section: Resultsmentioning
confidence: 99%
“…Bhuiyan et al (2008) and Togay, Togay and Dogan (2008a) obtained maximum seed yield and aboveground biomass production of mung bean and lentils, respectively, after using phosphorus application rates associated with molybdenum fertilization. Fertilization with P and Mo also had a positive effect on edible bean and soybean yield in areas of the Brazilian Cerrado (Araújo et al, 2009;Matoso;Kusdra, 2014;Vieira et al, 2016;Oliveira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…angulata plants, the highest estimated content was 11.72 mg g -1 MF for the Mo of rate 0.011 mg dm -3 (Figure 6a). Oliveira et al (2017) found that the results of protein Increases in protein and amino acid contents were found up to the Mo rate of 0.01 mg dm -3 (Figure 6). The plants were evaluated when they were in the reproductive phase and the NR activity was higher in roots than in leaves up to the Mo rate of 0.014 mg dm -3 (Figure 5); therefore, nitrogen assimilation may have been more efficient in the roots, resulting in formation of nitrogenous organic compounds, which may have been subsequently transferred to both the leaves and the reproductive parts.…”
Section: Resultsmentioning
confidence: 83%
“…Rossi et al (2012) obtained a yield of 3423 kg ha -1 with application of 55.7 g ha -1 Mo, obtaining a crop yield gain of 37% over the control treatment. Oliveira et al (2017), working at rates of 400 and 800 g ha -1 applied via leaf spray at stages R3 and R6, found no effect on crop yield. Table 3 presents the data on calcium, magnesium, potassium and nitrogen removal.…”
Section: Resultsmentioning
confidence: 93%
“…Lopes et al (2016) found that the application of 80 g ha -1 Mo increased the amount of N and protein content in bean grains, differing from our study which found no effect on these variables by Mo applied individually. Oliveira et al (2017) found a linear increase in the protein content of soybean when they applied doses of 0 to 800 g ha -1 molybdenum via leaf spray.…”
Section: Treatmentsmentioning
confidence: 97%